Attachment and psychotherapy. (February 2019) - Slade, Arietta; Holmes, Jeremy
Highlights: Many psychotherapy patients have insecure and particularly disorganized attachments. The patient therapist relationship has many features of an attachment relationship. The therapist as secure base serves as a potential agent of change. Different patterns of attachment require distinct modes of therapeutic intervention. Therapists' attachment orientation and mentalizing capacities are crucial to outcomes. Abstract : Attachment theory provides a model for understanding (1) development within the context of the child's primary, and formative relationships, and (2) an adult's orientation toward lifelong intimate connections, social relationships, and autonomous exploration. Psychotherapy researchers have linked measures of patient attachment with therapeutic alliance, process, and outcomes. Studies of ruptures and discourse analysis distinguish in-session behaviors associated with different patterns of insecure attachments, and identify distinct ways of working with them. The therapist's own attachment organization and mentalizing capacity also play a significant role in therapeutic success. The key tenets of attachment-informed psychotherapy are: (1) the therapist–patient attachment relationship is central to promoting change, (2) the in vivo recognition of attachment dynamics during therapy guides formulation and intervention, and (3) therapy can reshape attachment dynamics.